Supporting the Development of Autonomous Learning Using the internet in a Digital Age: Building Independent Language Learning and Learners’ Content Knowledge - Djoko Sutrisno (ETERNAL (English Teaching Journal), 2016)
In a fast-changing digital age, English language learners face growing demands to advance their familiarity with a ramification of on-line tools (Conole, 2008). technologies are changing the way we teach and learn in many respects. In teaching learning we aren't simplest cultivate the college students’ comprehensive characteristics however also increase their autonomous learning ability. because of this, the present article explored whether a developing independent gaining knowledge of using internet should improve the college students’ typical English overall performance greater correctly than the conventional English teaching placing. The aim of this experimental examine is to decide if internet may be an effective tool building language freshmen’ content expertise and writing talents. The study involved 15 advanced students of Ma’arif Nahdlatul Ulama University of Kebumen. Both quantitative and qualitative data collected from post‐surveys, transcribed digital recordings, blog reflections, and final interviews were analyzed. The findings provide the the statistics showed that internet empowered college students to apply their very own self‐expression and self-reflection  and that social interaction helped set up a feel of community wherein students have the ability in constructing building language learners’ content knowledge